Indian Dermoscopic Study of Forty Six Cases of Lichen Planus Pigmentosus - New Dermoscopy Signs Discovered - Rajendra Kumar Sharma, Rahul Kumar Sharma, (International Journal of Innovative Research in Medical Science, 2018)
Lichen planus pigmentosus (LPP) is a atypical pigmented variety of lichen planus. Lichen planus pigmentosus is an unpredictable relapsing idiopathic dermatosis with periods of activation and remission with poor response to treatment and may leads to cosmetically disfiguring post inflammatory pigmentation. Aim - To study dermoscopic features of untreated cases of Lichen planus pigmentosus. Study subjects - All the patients who attended the dermatology clinic from November 2015 to November 2017 with the clinical diagnosis of LPP and who fulfilled the inclusion and exclusion criteria. Methodology - All the patients who attended the dermatology clinic with the diagnosis of LPP were examined by a dermatoscope. Dermoscopy was performed with DL4 dermatoscope. The images were further magnified with smart phone. Results - Our study showed various dermoscopic signs in cases of LPP like annular granular pattern (35 cases), annular globular pattern (5 cases), homogeneous brown pigmentation (12 cases), homogeneous brownish black pigmentation (8 cases), brownish ovoid nests (3 cases), bluish blackish fine dots (4 cases), Wickham’s striae(2 cases) and pigmented targetoid globules(3 cases). Discussion - Dermatoscope is an indispensible valuable tool in clinical practice which helps in making early lucid diagnosis of LPP with very high accuracy. Our study showed that annular granular pattern is the commonest pattern in Indian LPP cases followed by homogeneous brown pigmentation. In our Indian LPP dermoscopy study we discovered three novel dermoscopic signs which includes brownish globular nests, pigmented targetoid globules and bluish blackish fine dots. In our study we got few unique cases where Wickham’s striae was also present with other dermoscopic signs which supports the link of LPP to lichen planus. Dermatoscopic diagnosis of LPP is made by combination of various signs and should not be dependent on the presence of single marker.